2008
DOI: 10.1210/er.2007-0023
|View full text |Cite
|
Sign up to set email alerts
|

Glucolipotoxicity: Fuel Excess and β-Cell Dysfunction

Abstract: Glucotoxicity, lipotoxicity, and glucolipotoxicity are secondary phenomena that are proposed to play a role in all forms of type 2 diabetes. The underlying concept is that once the primary pathogenesis of diabetes is established, probably involving both genetic and environmental forces, hyperglycemia and very commonly hyperlipidemia ensue and thereafter exert additional damaging or toxic effects on the beta-cell. In addition to their contribution to the deterioration of beta-cell function after the onset of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
809
3
20

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 967 publications
(848 citation statements)
references
References 197 publications
16
809
3
20
Order By: Relevance
“…We propose, therefore, that the induction of IL-1β and downstream chemokines and cytokines by saturated NEFA results in mild islet inflammation in type 2 diabetes, but that this does not directly contribute to beta cell dysfunction and apoptosis. ER stress [31] and other signalling pathways [55] contribute to lipotoxicity in human islets in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We propose, therefore, that the induction of IL-1β and downstream chemokines and cytokines by saturated NEFA results in mild islet inflammation in type 2 diabetes, but that this does not directly contribute to beta cell dysfunction and apoptosis. ER stress [31] and other signalling pathways [55] contribute to lipotoxicity in human islets in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that insulin secretion is impaired in type 2 diabetes [1,[29][30][31]. In addition, it was suggested that insulin signal transduction is perturbed in diabetic beta cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to accumulation of misfolded proteins, most importantly proinsulin, resulting in ER stress [54,55]. This, together with oxidative stress elicited by excessive mitochondrial generation of reactive oxygen species, leads to beta cell dysfunction [56,57]. The latter is the driving force for progression from obesity to diabetes.…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%